Studi Kasus: Penerapan Tema Menjadi Warga Digital Tular Nalar dalam Pembelajaran di Sekolah Melalui Flipped Classroom - Heni Mulyati; Catur Yoga Meiningdias (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. The number of hoaxes circulating in the community is one of the problems in the current era of information flooding. One of the efforts to prevent the circulation of hoaxes is critical thinking. Mafindo through the tularnalar.id website seeks to educate the public to be able to think critically through eight specific themes. One of the themes raised on the Tular Nalar website is Internet and Active Citizenship. This article is a case study of the application of the theme of Internet and Active Citizenship in learning in schools. The subject that is applied is class X informatics. The author changes the old pattern of learning to a new pattern that is more dynamic and utilizes online technology. The author integrates the materials and videos on the Tular Nalar website with learning at school through the flipped classroom model. Students independently read, observe, reflect, and give their opinions in the digital space. The result is that students understand how to communicate ethically on social media and are able to answer questions in the comments column. In addition, students ask questions and express opinions in the Google Meet discussion room. The interactions formed can improve students’ critical thinking skills. Abstrak. Banyaknya hoaks yang beredar di masyarakat menjadi salah satu masalah di era banjir informasi saat ini. Salah satu upaya menangkal peredaran hoaks adalah berpikir kritis. Mafindo melalui situs tularnalar.id berupaya mengedukasi masyarakat agar mampu berpikir kritis melalui delapan tema spesifik. Salah satu tema yang diangkat dalam situs Tular Nalar adalah Menjadi Warga Digital. Artikel ini merupakan studi kasus penerapan tema Menjadi Warga Digital dalam pembelajaran di sekolah. Mata pelajaran yang menjadi penerapan adalah informatika kelas X. Penulis melakukan perubahan pola lama pembelajaran ke pola baru yang lebih dinamis dan memanfaatkan teknologi secara daring. Penulis mengintegrasikan materi dan video yang ada di situs Tular Nalar dengan pembelajaran di sekolah melalui model flipped classroom (kelas terbalik). Terdapat sejumlah pertanyaan untuk dijawab peserta didik. Peserta didik secara mandiri membaca, mengamati, merefleksi, dan memberikan opininya dalam ruang digital. Hasilnya adalah peserta didik paham bagaimana perilaku etis komunikasi di media sosial dan mampu menjawab pertanyaan di kolom komentar. Selain itu, peserta didik mengajukan pertanyaan dan menyampaikan opini di ruang diskusi Google Meet. Interaksi yang terbentuk tersebut dapat meningkatkan kemampuan berpikir kritis peserta didik.